Concepts of modern physics - Beiser, Arthur; Mahajan, Shobhit; Choudhary, S Rai. (New Delhi: Tata McGraw Hill Education Private Limited, 2006)
Aimed for students who already come from a basic background in calculus and fundamental physics, the book is designed in such a way that concepts are explained in a progressive and logical manner, thus ensuring that the student is not overloaded with excessive information. This text is segregated into numerous chapters, covering topics like nuclear transformations, cosmology, particle properties of waves, quantum mechanics, artificial radioactivity, the solid state, nuclear reactions, and others. To help in thorough comprehension of the matter, the book is interspersed with numerous solved and unsolved problems that range from simple to complex.
Appendix 587-606p.; References 607-608p.; Index 611-623p.
Keywords: Atomic structure; Modern physics; Quantum Mechanics; Relativity; General Science